PENGARUH KEGIATAN EKSTRAKURIKULER BERBASIS KEARIFAN LOKAL TARI GANDRUNG TERHADAP KEMAMPUAN MOTORIK KASAR PADA ANAK USIA 5-6 TAHUN TK ALIFIA TAHUN AKADEMIK 2025-2026 - Faisollah; Wijaya Adi Putra; Ratnasari Dwi Ade Chandra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to examine the effect of extracurricular activities based on local wisdom through Gandrung dance on the gross motor skills of children aged 5–6 years at TK Alifia in the 2025–2026 academic year. The study employed a quantitative approach using a quasi-experimental method with a one group pretest–posttest design. The research subjects consisted of 15 children aged 5–6 years selected using a saturated sampling technique. Data were collected through structured observation sheets covering indicators of movement coordination, balance, agility, and large muscle strength. The data were analyzed using descriptive and inferential statistics with a paired sample t-test. The results showed that the mean score of children’s gross motor skills increased from 54.20 in the pretest to 77.60 in the posttest. The t-test analysis revealed a significance value of p < 0.05, indicating a statistically significant difference in children’s gross motor skills before and after participating in the Gandrung dance extracurricular activities. It can be concluded that extracurricular activities based on local wisdom through Gandrung dance have a positive and significant effect on the gross motor skills of children aged 5–6 years. This study suggests that traditional dance activities can be effectively integrated into early childhood education programs to support gross motor development.